Production of milk peptides with antimicrobial and antioxidant properties through fungal proteases - Zanutto-Elgui, Mirella Rossitto [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Prado, Débora Zanoni do [UNESP]; Buzalaf, Marília Afonso Rabelo; Padilha, Pedro de Magalhães [UNESP]; Elgui de Oliveira, Deilson [UNESP]; Fleuri, Luciana Francisco [UNESP] (Elsevier, 2019)
Bioactive peptides can provide health benefits due to different mechanisms. The aims of the present study are to produce bioactive peptides from bovine and goat milk subjected to the proteolytic activity of Aspergillus oryzae and Aspergillus flavipes enzymes, as well as to assess their putative antimicrobial and antioxidant activity. Bioactive peptides were successfully generated from proteases of fungi cultivated in solid-state fermentation. The generated peptides were effective against all tested bacteria and fungi. There was antioxidant activity, up to 92.5% DPPH reduction and ORAC stabilization at 52.5 μmol μL−1 of Trolox Equivalent. The generation of milk-specific sequences peptides in the samples was obtained through 2D-PAGE fractioning followed by mass spectrometry (ESI-MS/MS). Based on results in the present study, milk bioactive peptides presenting broad antimicrobial action and antioxidant activity spectra can be cost-effectively produced through solid-state fermentation. The herein addressed approach can be valuable for the pharmaceutical and food industries.
Keywords: Agroindustrial wastes; Bioactive peptides; Biotechnology; Proteomics; Solid-state fermentation